2011
DOI: 10.1002/cmdc.201000456
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of Isoerianin Analogues as Promising Anticancer Agents

Abstract: The cytotoxic activity of a series of 23 new isoerianin derivatives with modifications on both the A and B rings was studied. Several compounds exhibited excellent antiproliferative activity at nanomolar concentrations against a panel of human cancer cell lines. The most cytotoxic compound, isoerianin (3), strongly inhibits tubulin polymerization in the micromolar range. Moreover, isoerianin leads to G2/M phase cell-cycle arrest in H1299 and K562 cancer cells, and strongly induces apoptosis. Isoerianin also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 31 publications
(62 reference statements)
1
86
0
Order By: Relevance
“…Thus, we have demonstrated that it is possible to replacet he Z-1,2-diarylethylene scaffold of CA-4 with 1,1-diarylethylene to give isoCA-4, as tructural isomer of CA-4, with biological activities similar to those of the natural product. [18,19,22] We next showedt hat it is possible to reduce the double bond of isoCA4t of urnish (AE)-isoerianin 2a, [20] which also displayed excellent anticancer activities similartothose of natural erianin. [23] We recently prepared azaisoerianin derivatives 3 and were pleased to observe that such compounds are as potent as their C-congeners.…”
Section: Combretastatinmentioning
confidence: 99%
“…Thus, we have demonstrated that it is possible to replacet he Z-1,2-diarylethylene scaffold of CA-4 with 1,1-diarylethylene to give isoCA-4, as tructural isomer of CA-4, with biological activities similar to those of the natural product. [18,19,22] We next showedt hat it is possible to reduce the double bond of isoCA4t of urnish (AE)-isoerianin 2a, [20] which also displayed excellent anticancer activities similartothose of natural erianin. [23] We recently prepared azaisoerianin derivatives 3 and were pleased to observe that such compounds are as potent as their C-congeners.…”
Section: Combretastatinmentioning
confidence: 99%
“…2,2225 We examined reactions of a variety of heteroaryl sulfides with 3,4,5-trimethoxyphenylzinc bromide, biasing our small library of analogues toward inclusion of the 3,4,5-trimethoxyphenyl scaffold, a privileged motif commonly found in anticancer compounds that target microtubules. 26,27 We were pleased to see that the corresponding arylzinc bromide reacts with a variety of in situ-formed heteroaryl sulfenyl chlorides to afford the respective trimethoxyphenyl-substituted thioethers in modest to good yields ( 24 – 27 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The cytotoxic activity of 12 newly synthesized triarylolefins against human colon carcinoma cell line (HCT-116) was firstly evaluated using isoCA-4 [33] and CA-4 [55] as reference compounds. The IC 50 values corresponding to the concentration of studied compounds leading to 50% decrease in HCT-116 cell growth are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The E-isomers display dramatically reduced inhibition of cancer cell growth and tubulin assembly [29]. In our efforts to discover novel tubulin assembly inhibitors [30e32], we recently found that isocombretastatin A-4 (isoCA-4), the third and "forgotten" structural isomer of the natural product, displayed biological activities comparable to that of CA-4 [33,34]. This substance having a 1,1-diarylethylene scaffold is easy to synthesize [35,36] at a multi grams scale without the need to control the olefin geometry.…”
Section: Introductionmentioning
confidence: 99%